Analysis of Work Life Balance Of Employees In Mining Company PT. Pertamina Hulu Rokan - Hadi Putra Yuza; Jaya Addin Linando (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to analyze the impact of work-life balance on employee performance in the mining sector, focusing on the Pertamina Hulu Rokan (PHR) company. This study uses a qualitative approach with an in-depth interview method with eight purposively selected informants, consisting of productive employees aged 20 to 60 years. The results of the study indicate that work-life balance has a significant influence on physical and mental well-being, job satisfaction, organizational commitment, and employee productivity. Factors such as age, worship, hobbies, gender, and healthy lifestyles play an important role in maintaining this balance. The implication of this study is the importance of companies implementing flexible and inclusive policies to support work-life balance, which can ultimately improve employee performance and reduce the risk of burnout and stress in a challenging work environment.